Evolving frontiers in bladder cancer immunotherapy: integrating BCG, immune checkpoints, viral vectors, nanotechnology, and CAR-based therapies - Di Spirito, Anna; Zuccolotto, Gaia; Tosi, Anna; Balkhi, Sahar; Rosato, Antonio; Baci, Denisa; Mortara, Lorenzo (Frontiers in Cell and Developmental Biology, 2025)
Bladder cancer (BC) remains a prevalent malignancy with high recurrence rates despite standard therapies. Bacille Calmette-Guérin (BCG) is the cornerstone of treatment for non-muscle-invasive bladder cancer (NMIBC); however, nearly half of patients experience relapse or develop resistance, highlighting the need for alternative strategies. Recent advances in immunotherapy have reshaped the therapeutic landscape. Immune checkpoint inhibitors (ICIs) restore T-cell function and show clinical activity in BCG-unresponsive disease. Viral vector–based approaches, including nadofaragene firadenovec and CG0070, provide localized immune activation, while cellular platforms such as CAR-T and CAR-NK therapies offer precision targeting of tumor antigens. Concurrently, nanotechnology-based delivery systems and antibody–drug conjugates (ADCs) enhance efficacy and safety by improving tumor-specific cytotoxicity. Collectively, these strategies signify a paradigm shift from traditional intravesical therapy toward personalized and durable immunotherapeutic interventions. Identification of predictive biomarkers and rational combination strategies will be critical to improving outcomes and guiding the future management of BC.